On the implementation of an analog ATPG: the nonlinear case - Wey, C.-L.; Saeks, R. (IEEE transactions on instrumentation and measurement, 1988)
In order to reduce the complexity of the fault diagnosis equations and still retain computational simplicity, a self-testing algorithm has been proposed and implemented on a VMS VAX 11/780 for linear circuits. A prototype implementation of such an algorithm for nonlinear circuits and systems is presented. The proposed analog automatic test program generator (AATPG) for nonlinear circuits and systems is divided into offline and online processes. Unlike the simulation of the pseudocircuits in the linear case, which can be achieved by a matrix/vector multiplication, the circuit simulator SPICE is used to simulate the nonlinear pseudocircuits. The automatic SPICE code generator required for this simulation is presented. The proposed AATPG for nonlinear circuits has been implemented on a VMS VAX 11/780. The actual test can be run in either a fully automatic mode or interactively.< >